ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERATAAN LABA (INCOME SMOOTHING) PADA SUB INDUSTRI MAKANAN OLAHAN YANG TERDAFTAR DI BEI PERIODE TAHUN 2019-2024 - Uray Ndaru Mustika; Rizani Ramadhan; Pramana Saputra; Bintoro Bagus Purmono (MANAJEMEN DEWANTARA, 2026)
This study aims to examine the factors affecting income smoothing practices among processed food companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2024 period, focusing on firm size, financial leverage, and profitability. This is a quantitative study using panel data that combines the time-series and cross-sectional dimensions. The population consists of processed food sub-industry companies listed on the IDX, and 15 companies were selected using a purposive sampling technique based on predetermined criteria. Income smoothing was measured using the Eckel Index, and the data were analyzed through multiple linear regression with SPSS version 25. The results show that firm size has a significant positive effect on income smoothing, while financial leverage has a significant negative effect. In contrast, profitability (Net Profit Margin) does not significantly affect income smoothing. These findings indicate that company scale and debt structure are more decisive in shaping income smoothing behavior than the level of profitability.